Transmigrated Mandibular Canine and Impacted Maxillary Canines – A Distinctive Case Report - Anu Babu; Prashanth Shenoy; Laxmikanth Chatra; Sajad Ahmad Buch (Journal of Indian Academy of Oral Medicine and Radiology)
Migration of teeth is a well-known phenomenon, but dental transmigration, that is, pre-eruptive shifting of teeth across the midline, is a rare anomaly. Transmigration occurs mainly in impacted teeth and is almost seen primarily in canines. Maxillary canines rarely transmigrate despite being impacted 20 times more than the mandibular canines. The transmigrated canines are usually asymptomatic, and initial panoramic radiographs are essential for their diagnosis. Three-dimensional cone beam computed tomography is considered more effective for the diagnosis of transmigrated canines since it can help in a more precise location of transmigrated teeth and give a detailed insight into adjacent roots, resorption, and calcific metamorphosis.